Shall we dance - RKO Radio Pictures; Turner Home Entertainment (Firm).; Warner Home Video (Firm). (Burbank, Calif. Distributed by Warner Home Video, 2005)
A ballet star (Astaire) and a musical revue sensation (Rogers) decide to wed and publicly divorce to quash persistent rumors of a secret marriage. Once tied, however, perhaps they shouldn't call the whole thing off.
Special features: commentary by songwriter, Hugh Martin and pianist, Kevin Cole ; new featurette, The Music of Shall We Dance ; musical short sheik to sheik ; classic cartoon, Toy Town Hall.
Originally released as a motion picture in 1937.
Library has: VDR-1652 (2 VCDs)
Photographer, David Abel ; editor, William Hamilton ; music, George Gershwin ; lyrics, Ira Gershwin.
Fred Astaire, Ginger Rogers, Edward Everett Horton, Eric Blore, Jerome Cowan.
English dialogue, English, French or Spanish subtitles ; closed-captioned.
Keywords: Married people -- Drama; Love -- Drama; Feature films; Musical films; Video recordings for the hearing impaired